Outcomes of Different Methods for Analysis of Biliary Brush Cytology and of Factors Associated with Positive Diagnosis in an Age-Dependent Retrospective Review - Costa,Mariana (2019)
Background and Aims: Brush cytology during endoscopic retrograde cholangiopancreatography (ERCP) is the most frequently used strategy for obtaining a tissue sample from an indeterminate biliary stricture. A recent study reported that age is a factor associated with positive yields, but further analysis of how age influences the results was lacking. We aimed to evaluate clinical effectiveness of biliary cytology and prognostic factors for a positive outcome, especially age. Methods: This study was a single-center, retrospective, clinical study of 77 consecutive patients who underwent brush cytology during ERCP to obtain a diagnosis of an indeterminate biliary stricture. We compared 2 routine cytology techniques: A (smear); B (centrifugation of the cytological material collected and the cut-off brush + cell block when sufficient amount of material was available). The data were collected aiming to compare the accuracy of the different techniques used and the prognostic factors affecting the outcome, with a particular focus on age. The yield for brush cytology was compared with the gold standard defined as either definitive histology or the long-term clinical course. Results: The overall accuracy of the 2 used methods was 75.3%. Sensitivity was 52.5%, specificity was 100%, positive predictive value was 100%, and negative predictive value was 66.1%. Although not statistically significant, there was a trend toward accuracy for method B compared with method A (80.4 vs. 65.4%; p = 0.153). Multiple logistic regression analysis showed that younger age was the only independent prognostic factor associated with a positive diagnosis (OR 0.95; 95% CI 0.90-0.99; p = 0.039). Receiver operating characteristic curves for age yielded an area under the curve value of 68.2%. On the basis of the Youden index, 69 years was found to be the optimal cutoff for age. Conclusions: In this series, the accuracy of routine biliary brush cytology was not equal for all methods and ages; in particular, younger patients (below 69 years) tended to have a higher probability of a correct diagnosis.